2016
DOI: 10.18388/abp.2015_1230
|View full text |Cite
|
Sign up to set email alerts
|

High density lipoprotein subfractions and paraoxonase 1 in children

Abstract: The Lipoprint system (Quantimetrix Corp., CA, USA), enables the determination of 10 high density lipoprotein (HDL) subfractions in contrast to the 5 HDL subfractions that can be determined by ultracentrifuge analysis. HDL subfractions, and their relationships to the arylesterase (PON1-A) and lactonase (PON1-L) activities of paraoxonase 1 (PON1), together with total-, very low density lipoprotein- and low density lipoprotein (LDL)-cholesterol and LDL subfractions were investigated in the serum of 27 mildly hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 46 publications
4
14
0
Order By: Relevance
“…Moreover, smaller HDL size and/or increased proportion of HDL 3 particles were associated with reduced PON1 activity . The associations between HDL‐cholesterol level and size heterogeneity, and PON1 activity and/or markers of inflammation observed in our studies were subsequently confirmed by several research groups while denied by others . A possible explanation for inconsistent data could have been attributed to different methodological approaches used to isolate HDL subclasses, disparities in substrates employed for PON1 activity determination and differences in the characteristics of study participants.…”
Section: Hdl Characteristics and Pon1 Activity—a Bridge Toward Hdl Fumentioning
confidence: 48%
See 1 more Smart Citation
“…Moreover, smaller HDL size and/or increased proportion of HDL 3 particles were associated with reduced PON1 activity . The associations between HDL‐cholesterol level and size heterogeneity, and PON1 activity and/or markers of inflammation observed in our studies were subsequently confirmed by several research groups while denied by others . A possible explanation for inconsistent data could have been attributed to different methodological approaches used to isolate HDL subclasses, disparities in substrates employed for PON1 activity determination and differences in the characteristics of study participants.…”
Section: Hdl Characteristics and Pon1 Activity—a Bridge Toward Hdl Fumentioning
confidence: 48%
“…28,29,32 The associations between HDL-cholesterol level and size heterogeneity, and PON1 activity and/or markers of inflammation observed in our studies were subsequently confirmed by several research groups [33][34][35] while denied by others. 36,37 A possible explanation for inconsistent data could have been attributed to different methodological approaches used to isolate HDL subclasses, disparities in substrates employed for PON1 activity determination and differences in the characteristics of study participants. Our data provided valuable information on the clinical significance of the advanced lipid profile and oxidative stress testing and its modulation in high-risk subjects.…”
Section: Hdl Characteristics and Pon1 Activity-a Bridge Toward Hdl mentioning
confidence: 99%
“…Moreover, a longer FA embedded in the membrane (e.g. DHA) contributes to the increased size of lipoprotein particles LDL and HDL characterized by an atheroprotective effect (Oravec et al 2011, Muchová et al 2016. In addition to the composition of FA, membrane fluidity is influenced also by other factors, e.g.…”
Section: Why Are Omega-3 Fas Important For Physical and Mental Health?mentioning
confidence: 99%
“…Oravec et al (2011) [ 20 ] consider intermediate HDL (I-HDL4-7) subfractions as anti-atherogenic part of HDL family. Based on our previous results, we hypothesize that I-HDL4 and I-HDL-5, which are adjacent to large HDL subfractions, are rather non-atherogenic and I-HDL6 a 7, which are adjacent to small HDL subfractions are rather atherogenic [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…No significant association between PON1-A and the HDL subfractions in 27 mildly hypercholesterolemic children was found. In contrast, PON1-L activity positively correlated with the antiatherogenic large HDL1 subfraction and negatively with intermediate HDL subfractions 4, 5, and 6 [ 21 ].…”
Section: Introductionmentioning
confidence: 99%